module GpdCont.TwoCategory.Displayed.LaxFunctor where
open import GpdCont.Prelude
open import GpdCont.TwoCategory.Base
open import GpdCont.TwoCategory.LaxFunctor
open import GpdCont.TwoCategory.Displayed.Base
open TotalTwoCategory using (∫)
module _
{ℓoC ℓoCᴰ ℓoD ℓoDᴰ}
{ℓhC ℓhCᴰ ℓhD ℓhDᴰ}
{ℓrC ℓrCᴰ ℓrD ℓrDᴰ}
{C : TwoCategory ℓoC ℓhC ℓrC}
{D : TwoCategory ℓoD ℓhD ℓrD}
(F : LaxFunctor C D)
(Cᴰ : TwoCategoryᴰ C ℓoCᴰ ℓhCᴰ ℓrCᴰ)
(Dᴰ : TwoCategoryᴰ D ℓoDᴰ ℓhDᴰ ℓrDᴰ)
where
private
ℓ : Level
ℓ = ℓMax ℓoC ℓoCᴰ ℓoD ℓoDᴰ ℓhC ℓhCᴰ ℓhD ℓhDᴰ ℓrC ℓrCᴰ ℓrD ℓrDᴰ
module C = TwoCategory C
module D = TwoCategory D
open module F = LaxFunctor F hiding (₀ ; ₁ ; ₂)
module Cᴰ = TwoCategoryᴰ Cᴰ
module Dᴰ = TwoCategoryᴰ Dᴰ
record LaxFunctorᴰ : Type ℓ where
no-eta-equality
field
F-obᴰ : {x : C.ob}
→ Cᴰ.ob[ x ] → Dᴰ.ob[ F.₀ x ]
F-homᴰ : {x y : C.ob} {f : C.hom x y}
→ {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]}
→ Cᴰ.hom[ f ] xᴰ yᴰ → Dᴰ.hom[ F.₁ f ] (F-obᴰ xᴰ) (F-obᴰ yᴰ)
F-relᴰ : {x y : C.ob} {f g : C.hom x y} {r : C.rel f g}
→ {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]}
→ {fᴰ : Cᴰ.hom[ f ] xᴰ yᴰ}
→ {gᴰ : Cᴰ.hom[ g ] xᴰ yᴰ}
→ Cᴰ.rel[ r ] fᴰ gᴰ → Dᴰ.rel[ F.₂ r ] (F-homᴰ fᴰ) (F-homᴰ gᴰ)
₀ = F-obᴰ
₁ = F-homᴰ
₂ = F-relᴰ
field
F-rel-idᴰ : {x y : C.ob} {f : C.hom x y}
→ {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]}
→ {fᴰ : Cᴰ.hom[ f ] xᴰ yᴰ}
→ PathP (λ i → Dᴰ.rel[ F-rel-id {f = f} i ] (F-homᴰ fᴰ) (F-homᴰ fᴰ))
(F-relᴰ (Cᴰ.id-relᴰ fᴰ))
(Dᴰ.id-relᴰ (F-homᴰ fᴰ))
F-rel-transᴰ : {x y : C.ob} {f g h : C.hom x y} {r : C.rel f g} {s : C.rel g h}
→ {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]}
→ {fᴰ : Cᴰ.hom[ f ] xᴰ yᴰ}
→ {gᴰ : Cᴰ.hom[ g ] xᴰ yᴰ}
→ {hᴰ : Cᴰ.hom[ h ] xᴰ yᴰ}
→ (rᴰ : Cᴰ.rel[ r ] fᴰ gᴰ)
→ (sᴰ : Cᴰ.rel[ s ] gᴰ hᴰ)
→ PathP (λ i → Dᴰ.rel[ F-rel-trans r s i ] (F-homᴰ fᴰ) (F-homᴰ hᴰ))
(F-relᴰ (rᴰ Cᴰ.∙ᵥᴰ sᴰ))
((F-relᴰ rᴰ) Dᴰ.∙ᵥᴰ (F-relᴰ sᴰ))
field
F-trans-laxᴰ : {x y z : C.ob} {f : C.hom x y} {g : C.hom y z}
→ {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]} {zᴰ : Cᴰ.ob[ z ]}
→ (fᴰ : Cᴰ.hom[ f ] xᴰ yᴰ)
→ (gᴰ : Cᴰ.hom[ g ] yᴰ zᴰ)
→ Dᴰ.rel[ F-trans-lax f g ]
((F-homᴰ fᴰ) Dᴰ.∙₁ᴰ (F-homᴰ gᴰ))
(F-homᴰ (fᴰ Cᴰ.∙₁ᴰ gᴰ))
F-trans-lax-naturalᴰ : {x y z : C.ob} {f₁ f₂ : C.hom x y} {g₁ g₂ : C.hom y z} {r : C.rel f₁ f₂} {s : C.rel g₁ g₂}
→ {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]} {zᴰ : Cᴰ.ob[ z ]}
→ {f₁ᴰ : Cᴰ.hom[ f₁ ] xᴰ yᴰ}
→ {f₂ᴰ : Cᴰ.hom[ f₂ ] xᴰ yᴰ}
→ {g₁ᴰ : Cᴰ.hom[ g₁ ] yᴰ zᴰ}
→ {g₂ᴰ : Cᴰ.hom[ g₂ ] yᴰ zᴰ}
→ (rᴰ : Cᴰ.rel[ r ] f₁ᴰ f₂ᴰ)
→ (sᴰ : Cᴰ.rel[ s ] g₁ᴰ g₂ᴰ)
→ PathP (λ i → Dᴰ.rel[ F-trans-lax-natural r s i ] ((F-homᴰ f₁ᴰ) Dᴰ.∙₁ᴰ (F-homᴰ g₁ᴰ)) (F-homᴰ (f₂ᴰ Cᴰ.∙₁ᴰ g₂ᴰ)))
((F-relᴰ rᴰ Dᴰ.∙ₕᴰ F-relᴰ sᴰ) Dᴰ.∙ᵥᴰ (F-trans-laxᴰ f₂ᴰ g₂ᴰ))
(F-trans-laxᴰ f₁ᴰ g₁ᴰ Dᴰ.∙ᵥᴰ F-relᴰ (rᴰ Cᴰ.∙ₕᴰ sᴰ))
F-id-laxᴰ : {x : C.ob} (xᴰ : Cᴰ.ob[ x ])
→ Dᴰ.rel[ F-id-lax x ] (Dᴰ.id-homᴰ (F-obᴰ xᴰ)) (F-homᴰ (Cᴰ.id-homᴰ xᴰ))
field
F-assocᴰ : {x y z w : C.ob} {f : C.hom x y} {g : C.hom y z} {h : C.hom z w}
→ {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]} {zᴰ : Cᴰ.ob[ z ]} {wᴰ : Cᴰ.ob[ w ]}
→ (fᴰ : Cᴰ.hom[ f ] xᴰ yᴰ)
→ (gᴰ : Cᴰ.hom[ g ] yᴰ zᴰ)
→ (hᴰ : Cᴰ.hom[ h ] zᴰ wᴰ)
→ PathP (λ i → Dᴰ.rel[ F-assoc f g h i ] (Dᴰ.comp-hom-assocᴰ (F-homᴰ fᴰ) (F-homᴰ gᴰ) (F-homᴰ hᴰ) i) (F-homᴰ (Cᴰ.comp-hom-assocᴰ fᴰ gᴰ hᴰ i)))
((F-trans-laxᴰ fᴰ gᴰ Dᴰ.∙ₕᴰ Dᴰ.id-relᴰ (F-homᴰ hᴰ)) Dᴰ.∙ᵥᴰ F-trans-laxᴰ (fᴰ Cᴰ.∙₁ᴰ gᴰ) hᴰ)
((Dᴰ.id-relᴰ (F-homᴰ fᴰ) Dᴰ.∙ₕᴰ F-trans-laxᴰ gᴰ hᴰ) Dᴰ.∙ᵥᴰ F-trans-laxᴰ fᴰ (gᴰ Cᴰ.∙₁ᴰ hᴰ))
F-unit-leftᴰ : {x y : C.ob} {f : C.hom x y} {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]}
→ (fᴰ : Cᴰ.hom[ f ] xᴰ yᴰ)
→ PathP (λ i → Dᴰ.rel[ F-unit-left f i ] (Dᴰ.comp-hom-unit-leftᴰ (F-homᴰ fᴰ) i) (F-homᴰ (Cᴰ.comp-hom-unit-leftᴰ fᴰ i)))
((F-id-laxᴰ xᴰ Dᴰ.∙ₕᴰ Dᴰ.id-relᴰ (F-homᴰ fᴰ)) Dᴰ.∙ᵥᴰ F-trans-laxᴰ (Cᴰ.id-homᴰ xᴰ) fᴰ)
(Dᴰ.id-relᴰ (F-homᴰ fᴰ))
F-unit-rightᴰ : {x y : C.ob} {f : C.hom x y} {xᴰ : Cᴰ.ob[ x ]} {yᴰ : Cᴰ.ob[ y ]}
→ (fᴰ : Cᴰ.hom[ f ] xᴰ yᴰ)
→ PathP (λ i → Dᴰ.rel[ F-unit-right f i ] (Dᴰ.comp-hom-unit-rightᴰ (F-homᴰ fᴰ) i) (F-homᴰ (Cᴰ.comp-hom-unit-rightᴰ fᴰ i)))
((Dᴰ.id-relᴰ (F-homᴰ fᴰ) Dᴰ.∙ₕᴰ F-id-laxᴰ yᴰ) Dᴰ.∙ᵥᴰ F-trans-laxᴰ fᴰ (Cᴰ.id-homᴰ yᴰ))
(Dᴰ.id-relᴰ (F-homᴰ fᴰ))
toTotalFunctor : LaxFunctor (∫ C Cᴰ) (∫ D Dᴰ)
toTotalFunctor .LaxFunctor.F-ob (x , xᴰ) .fst = F-ob x
toTotalFunctor .LaxFunctor.F-ob (x , xᴰ) .snd = F-obᴰ xᴰ
toTotalFunctor .LaxFunctor.F-hom (f , fᴰ) .fst = F-hom f
toTotalFunctor .LaxFunctor.F-hom (f , fᴰ) .snd = F-homᴰ fᴰ
toTotalFunctor .LaxFunctor.F-rel (r , rᴰ) .fst = F-rel r
toTotalFunctor .LaxFunctor.F-rel (r , rᴰ) .snd = F-relᴰ rᴰ
toTotalFunctor .LaxFunctor.F-rel-id i .fst = F-rel-id i
toTotalFunctor .LaxFunctor.F-rel-id i .snd = F-rel-idᴰ i
toTotalFunctor .LaxFunctor.F-rel-trans (r , rᴰ) (s , sᴰ) i .fst = F-rel-trans r s i
toTotalFunctor .LaxFunctor.F-rel-trans (r , rᴰ) (s , sᴰ) i .snd = F-rel-transᴰ rᴰ sᴰ i
toTotalFunctor .LaxFunctor.F-trans-lax (f , fᴰ) (g , gᴰ) .fst = F-trans-lax f g
toTotalFunctor .LaxFunctor.F-trans-lax (f , fᴰ) (g , gᴰ) .snd = F-trans-laxᴰ fᴰ gᴰ
toTotalFunctor .LaxFunctor.F-trans-lax-natural (r , rᴰ) (s , sᴰ) i .fst = F-trans-lax-natural r s i
toTotalFunctor .LaxFunctor.F-trans-lax-natural (r , rᴰ) (s , sᴰ) i .snd = F-trans-lax-naturalᴰ rᴰ sᴰ i
toTotalFunctor .LaxFunctor.F-id-lax (x , xᴰ) .fst = F-id-lax x
toTotalFunctor .LaxFunctor.F-id-lax (x , xᴰ) .snd = F-id-laxᴰ xᴰ
toTotalFunctor .LaxFunctor.F-assoc (f , fᴰ) (g , gᴰ) (h , hᴰ) i .fst = F-assoc f g h i
toTotalFunctor .LaxFunctor.F-assoc (f , fᴰ) (g , gᴰ) (h , hᴰ) i .snd = F-assocᴰ fᴰ gᴰ hᴰ i
toTotalFunctor .LaxFunctor.F-unit-left (f , fᴰ) i .fst = F-unit-left f i
toTotalFunctor .LaxFunctor.F-unit-left (f , fᴰ) i .snd = F-unit-leftᴰ fᴰ i
toTotalFunctor .LaxFunctor.F-unit-right (f , fᴰ) i .fst = F-unit-right f i
toTotalFunctor .LaxFunctor.F-unit-right (f , fᴰ) i .snd = F-unit-rightᴰ fᴰ i